The role of Kufi school in shaping Hanafi’s mazhab (Journal of Philosophy, Culture and Political Science, 2016)
This article discusses the period of creation Kufic school of fiqh, and provides reasonable evidence that ever was with the Prophet Muhammad (peace and blessings of Allah) faithful companions (Sahaabah) and their famous followers (Taabi’een) is the founder of the school. The article said that the Muslims of Kufa differed from their compatriots in terms of knowledge of hadith and fiqh, explores the basic concepts of religion and to make legal decisions. In addition, we are talking about the scientific methodology proposed by Hadith scholars of Kufa, having a special criteria for the study and adoption of hadith.